Answer:
x= -3 x = 1/2 x=-2
Step-by-step explanation:
f(x)=(x+3) (2x-1)(x+2)
Set equal to zero
0 =(x+3) (2x-1)(x+2)
Using the zero product property
x+3 =0 2x-1 =0 x+2 =0
x= -3 2x =1 x = -2
x= -3 x = 1/2 x=-2
Answer:
1
Step-by-step explanation:
It's the correct spelling.
Answer: 1
Step-by-step explanation:
8/-4 ÷ -3/9
8/-4 × 9/ -3 = 6
answer: dividing the number by 100
100 ×100= 100000
100000÷100
100
D. because for every hour it goes down 5 degrees and since there is a 1 hour gap in between 7 am and 9 am